Digital Democracy and Open Finance Technology: Advancing Transparency and Consumer Digital Rights - Yudhi Priyo Amboro; Peter Macnico; Winsherly Tan; Mimi Sintia Mohd Bajury (Lex Publica, 2025)
This research explores the role of Open Finance in strengthening Indonesia’s digital democracy, with a focus on transparency, digital consumer rights, and data oversight. While Open Finance has the potential to increase financial inclusion through the integration of alternative data for marginalized groups, such as MSMEs and rural communities, the practice of massive data sharing risks threatening democratic principles, such as data being vulnerable to mass surveillance, algorithmic discrimination, and weak regulatory accountability. A comparative analysis of the UK (CMA Order) and Australian (Consumer Data Rights) regulatory models highlight the importance of algorithmic transparency, granular consumer control over data, and public participation mechanisms in policymaking. In Indonesia, the suboptimal implementation of the Personal Data Protection Law (PDP Law), the digital literacy gap, and disparities in technological infrastructure are key challenges.